2010
DOI: 10.1007/s00300-010-0779-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and salinity on vital biological functions of the Antarctic crustacean Serolis polita

Abstract: EVects of temperature rise (from 0 to +5°C) and salinity decline (from 34 to 30 psu) on vital biological functions of the Antarctic isopod Serolis polita were studied in laboratory experiments. Behavioural reactions to food odour, as well as righting responses and reburying in the sediments, were measured. Both temperature increase and salinity decline impaired the ability of S. polita to perform these biological functions critical for their long-term survival, by lowering the number of isopods able to right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Species adapted to broad variations of environmental factors, such as the temperate shrimp Palaemon peringuery, for instance, did not show any significant differences in oxygen consumption when data measured at the same temperature over a salinity range of 15 to 35 were compared (ALLAN et al, 2006). Antarctic ectotherms may present distinct adaptive ability depending on the species (WILSON et al, 2002;JANECKI et al, 2010;EVANS et al, 2012) and their respective habitats. Coastal water Antarctic ectotherms, however, seem to have a low capacity to survive during long periods at temperatures higher than the environmental average, even if they are able to tolerate this same temperature during a certain period of time (PÖRTNER et al, 2001;PECK, 2005;TOMANEK, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Species adapted to broad variations of environmental factors, such as the temperate shrimp Palaemon peringuery, for instance, did not show any significant differences in oxygen consumption when data measured at the same temperature over a salinity range of 15 to 35 were compared (ALLAN et al, 2006). Antarctic ectotherms may present distinct adaptive ability depending on the species (WILSON et al, 2002;JANECKI et al, 2010;EVANS et al, 2012) and their respective habitats. Coastal water Antarctic ectotherms, however, seem to have a low capacity to survive during long periods at temperatures higher than the environmental average, even if they are able to tolerate this same temperature during a certain period of time (PÖRTNER et al, 2001;PECK, 2005;TOMANEK, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The coastal slope is steep and reaches a depth of 500m in the central regions, like a fjord with a great U-shaped valley (RAKUSA-SUSZCZEWSKI, 1980;MONTONE, 2006;MONTONE et al, 2013). During summer, at the surface, mean sea water salinity is 34 and temperature may range from -0.2°C to 5.3°C; at the bottom, mean salinity is 34.5 and temperature varies from -0.4°C to 0.9°C (PRUSZAK, 1980;JAZDZESKI et al, 1986).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species have been shown to be vulnerable to largescale environmental changes observed in the region of the West Antarctic Peninsula (Ingels et al 2012). Specifically, the mobility, physiology and development of benthic isopods may be affected by modification of hydrological and sedimentary regimes (Young et al 2006;Janecki et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A cyclic decrease of water salinity led to a signifi cant increase in the mortality of halophiles. Experimental studies carried out by Janecki et al (2010) showed great vulnerability of ocean organisms to water salinity decline. Organic matter carried from the ocean to the shores of Admiralty Bay was the subject of detailed analyses.…”
Section: Characteristics Of the Ecology Lagoonmentioning
confidence: 99%